Other Headings: Ben Jelloun, Derrida, Sansal and the Critique of Europe. Issue 2 (3rd March 2016) - Kaiser, Birgit; Thiele, Kathrin
Abstract : This essay diffracts the question of the heading of Europe that Derrida asked in 1990. We do so through the prism of harraga presented in Tahar Ben Jelloun's Leaving Tangiers and Boualem Sansal's Harraga. Although Europe as the capital has been 'de-identified' (Derrida1992, 75) in the wake of decolonization and postcolonial critique, it still has to be de-identified always anew. Something has been promised in its name and is, we suggest, currently most forcefully reclaimed by people who 'burn up the road'. Listening to these claims is vital for any future 'Europe' because the responses currently presented by 'Europe' are still either self-identification and closure or aversion from Europe altogether. With reference to Derrida, this essay insists on the necessity to take note of and affirm that Europe must 'open itself onto the other shore of another heading'. Derrida was hopeful ('that is already at work anyway'), underneath and alongside the closure of borders since the early 1990s and the increase in clandestine migration. Although we see mainly symptoms of radical closure, with Derrida and the harragas this essay asserts it can be otherwise – that it is Europe's brutal failure to ignore this call of the heading of the others, forestalling any chance for an 'other of the heading'. It is thus 'Europe's' duty to listen to the (re)call of these others.